Microbial Interactions in Response to Sulfide Effect on Mesophilic Bacterial Mixed Culture (BMC) Growth - Ahmad, Mani Malam; Abdul Aziz, Mohd Azoddein; Mior Ahmad Khushairi, Mohd Zahari; Mazrul Nizam, Abu Seman; Mohammad Saedi, Jami (Penerbit Akademia Baru, 2017)
The inhibitory effect of hydrogen sulfide has been indicated to activate a sequence of response mechanism through microbial mutual interactions. Bacterial mixed-culture (BMC) consortium has been found to reduce the complexity of oxidative stress through mutual interactions of helper bacteria thereby facilitating the growth of the disadvantaged inoculum. The potential sulfide bioxidation of strain one (S1) and strain two (S2) mixed-culture bacterial consortiums were tested at different sulfide level within a 24-hour period. The present study was therefore able to decipher the potential of BMC to oxidation of a fragmented sulfide concentration in an oxygen deficient condition of an incubator shake flasks using a single nutrient composition under defined operational parameters of pH, temperature, acclimatization time and agitation. Results indicated an overwhelming oxidation of varying sulfide concentration which is an energy source for biomass synthesis. This correspond to an average cell biomass increase at optical density greater than one after 6 hrs of seeding, which later almost doubled at 24 hrs period. Furthermore, BMC degraded on average, 97.50%, 96.67% and 93% of the different concentrations of sulfide in 24 hrs of inoculation, respectively. Sulfide oxidation and uptake were in ascending order 200 ppm S2- L1-d1-> 300 ppm S2-L1-d1-> 500, ppm S2- L1-d1. Overall, the result signifies the synergistic complementary effects of helper bacteria in the consortium which lessen the oxidative stress, thus ensuring the growth and removal in both isolates. The mixed-culture consortium, S1 and S2, showcased an expeditious growth and sulfide degradation in chemically deficient medium and operational parameters of shake flasks, demonstrating that the consortium would be applicable to handle wastewater laden with H2S.